Towards a ‘Benchmarking Raster’: a Selection of Indicators to Measure and Assess Policies for Cultural and Creative Industries - Montalto, Valentina; Iglesias, Maria; Kern, Philippe (Quaestiones Geographicae, 2012)
Research has devoted considerable attention to the contribution of cultural and creative industries (CCIs) to economic growth and innovation. Measuring and evaluative tools have played an increasingly important role in meeting the demand for the accountability of public money supporting this sector. Nevertheless, creativity remains an elusive subject for policy-makers. One of the major obstacles in adopting CCI policies is the difficulty in apprehending the value of support actions for cultural and creative enterprises. The present research is a first attempt to create a harmonised and simple set of indicators (the ‘benchmarking raster’) to assess local policies targeting economic development of CCIs. It has been completed in the framework of the INTERREG- funded CREA.RE network with the aim to encourage the authorities of small and medium-sized cities and regions to further invest Structural Funds in CCIs. It is also expected to contribute to CCI-focused economic development strategies (or Smart Specialisation Strategies).